Whole-body and adipose tissue-specific mechanisms underlying the metabolic effects of fibroblast growth factor 21 in the Siberian hamster - Jo E. Lewis; Chloe Monnier; Hayley Marshall; Maxine Fowler; Rebecca Green; Scott Cooper; Aristeidis Chiotellis; Jeni Luckett; Alan C. Perkins; Tamer Coskun; Andrew C. Adams; Ricardo J. Samms; et al. (Molecular Metabolism, 2020)
Objective: Fibroblast growth factor 21 (FGF21) has been shown to rapidly lower body weight in the Siberian hamster, a preclinical model of adiposity. This induced negative energy balance mediated by FGF21 is associated with both lowered caloric intake and increased energy expenditure. Previous research demonstrated that adipose tissue (AT) is one of the primary sites of FGF21 action and may be responsible for its ability to increase the whole-body metabolic rate. The present study sought to determine the relative importance of white (subcutaneous AT [sWAT] and visceral AT [vWAT]), and brown (interscapular brown AT [iBAT]) in governing FGF21-mediated metabolic improvements using the tissue-specific uptake of glucose and lipids as a proxy for metabolic activity. Methods: We used positron emission tomography-computed tomography (PET-CT) imaging in combination with both glucose (18F-fluorodeoxyglucose) and lipid (18F-4-thiapalmitate) tracers to assess the effect of FGF21 on the tissue-specific uptake of these metabolites and compared responses to a control group pair-fed to match the food intake of the FGF21-treated group. In vivo imaging was combined with ex vivo tissue-specific functional, biochemical, and molecular analyses of the nutrient uptake and signaling pathways. Results: Consistent with previous findings, FGF21 reduced body weight via reduced caloric intake and increased energy expenditure in the Siberian hamster. PET-CT studies demonstrated that FGF21 increased the uptake of glucose in BAT and WAT independently of reduced food intake and body weight as demonstrated by imaging of the pair-fed group. Furthermore, FGF21 increased glucose uptake in the primary adipocytes, confirming that these in vivo effects may be due to a direct action of FGF21 at the level of the adipocytes. Mechanistically, the effects of FGF21 are associated with activation of the ERK signaling pathway and upregulation of GLUT4 protein content in all fat depots. In response to treatment with FGF21, we observed an increase in the markers of lipolysis and lipogenesis in both the subcutaneous and visceral WAT depots. In contrast, FGF21 was only able to directly increase the uptake of lipid into BAT. Conclusions: These data identify brown and white fat depots as primary peripheral sites of action of FGF21 in promoting glucose uptake and also indicate that FGF21 selectively stimulates lipid uptake in brown fat, which may fuel thermogenesis. Keywords: FGF21, β-klotho, White adipose tissue, Brown adipose tissue, Glucose uptake, Lipid uptake